Analysis of Digital Readiness in the Social Assistance Distribution System with the Unified Theory of Acceptance and Use of Technology (UTAUT) - Adiyono, Soni; Latifah, Noor; Laily Fithri, Diana (Politeknik Negeri Batam, 2025)
The adoption of digital systems for social assistance distribution has become increasingly vital in enhancing efficiency and accessibility. This study examines the acceptance of such a system using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, analyzing six key constructs: Performance Expectancy (PE), Effort Expectancy (EX), Social Influence (SI), Facilitating Conditions (FC), Behavioral Intention (BI), and Actual Use (AU). A total of 150 respondents participated in the survey, providing insights into their perceptions of the system. The findings indicate that Performance Expectancy (4.2) received the highest mean score, demonstrating that users perceive the system as beneficial in improving efficiency. Effort Expectancy (4.0) suggests that the system is easy to use, while Social Influence (3.8) highlights the moderate role of external encouragement. Facilitating Conditions (3.9) reveal the availability of infrastructure but also suggest areas for improvement. Additionally, Behavioral Intention (4.1) and Actual Use (4.0) indicate strong user commitment toward system utilization. The study contributes to the understanding of digital technology adoption in social welfare programs and provides recommendations for optimizing system implementation. Future research should explore the long-term impact of digital adoption, assess its effectiveness in different demographic groups, and integrate qualitative insights to deepen the understanding of user experiences. Additionally, expanding the analysis to include external factors such as policy support, economic conditions, and digital literacy could further enhance the model’s applicability.